Understanding differing conceptions of violence through Self–Other relations in Gandhi and Fanon. (June 2017) - Devare, Aparna
This article compares and contrasts Gandhi's and Fanon's views on violence by placing these ideas within a larger framework of how each viewed the Self and its relationship with the Other. I argue in the article that Gandhi did not view the Self as clearly separable from the Other; the Self was internal to the Other and hence violence to the Other would also affect the Self. This was one of the underlying reasons behind his adopting a philosophy of non-violence. In the case of Fanon, I argue that one can identify a "dominant" Fanon who makes a clear separation between Self and Other in contrast to Gandhi and hence can justify violence inflicted on the colonizer. But, the article also teases out a "marginal" or "Other" Fanon who comes much closer to Gandhi in the manner in which he views the Other as implicated within the Self particularly through his own lived experience, his activism, his views on psychiatry, and his other writings apart from Wretched of the Earth.